Scientific Communication 2.0: Features of Presenting Scientific Content on German Popular Science YouTube Channels - V. A. Andreeva; L. B. Kopchuk (Научный диалог)
The article is devoted to the feature’s analysis of the presentation of scientific content on the German-language popular science YouTube channels maiLab and Terra X Lesch & Co. It has been established that, in general, the popular science YouTube channels maiLab and Terra X Lesch & Co. are oriented towards the strategies and forms of presentation of scientific content adopted in the field of science: types of thematic progression characteristic of theoretical discourse (descriptive, explicative and argumentative) are used, as well as scheme of an argumentative statement. It is shown that, in contrast to the objectification mechanism of information exchange, which determines the presentation of scientific content within the scientific community, a personalization mechanism operates in the network of popular science communication, which is determined by the peculiarities of the interaction of the participants in network communication and the polymodality of the Internet as a medium. The authors consider in detail the techniques of intimization, emotionalization, dialogization, metaphorization, visualization and implementation of a narrative pattern. It is noted that these techniques allow bloggers to maintain the attention and interest of their channel subscribers, as well as simplify the presentation of scientific content, making it easier to understand. It is proved that the use of the strategy of personalization of information exchange, which is characteristic of mass media discourse, leads to a consistent violation of the prohibitions existing in theoretical discourse on any explicit manifestation of the subject of speech in a statement. The analysis of the material allows the authors to conclude about the active interaction of different discourses — theoretical and mass media — in their peripheral zones and describe the mechanisms of this interaction.